2010
DOI: 10.1002/imhj.20258
|View full text |Cite
|
Sign up to set email alerts
|

“Ghosts in the Nursery:” Infant sleep and sleep‐related cognitions of parents raised under communal sleeping arrangements

Abstract: In an experiment of nature, a normal cohort of parents who were raised under communal sleeping arrangements (CSA) in Israeli kibbutzim are raising their infants at home under home-based family sleeping arrangements. The present study focused on exploring the links between the early sleep experiences of CSA parents and their present sleep-related beliefs and behaviors. In particular, the study assessed whether the cognitions of CSA parents regarding infant sleep differ from cognitions of parents who were raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 73 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…A night-time experience characterized by parental inaccessibility and nonavailability, combined with exposure to numerous unfamiliar adults, was associated with increased risk of insecure attachments. In fact, some adults who had experienced such a setting in their childhood reported that they had no significant memory of their parents (Tikotzky, Sharabany, Hirsch, & Sadeh, 2010). Because the kibbutz made the group of children a family unit, some may have felt that the natural protection expected by the family was lacking.…”
Section: Group Care May Cause Psychological Harm Even In Typically De...mentioning
confidence: 99%
“…A night-time experience characterized by parental inaccessibility and nonavailability, combined with exposure to numerous unfamiliar adults, was associated with increased risk of insecure attachments. In fact, some adults who had experienced such a setting in their childhood reported that they had no significant memory of their parents (Tikotzky, Sharabany, Hirsch, & Sadeh, 2010). Because the kibbutz made the group of children a family unit, some may have felt that the natural protection expected by the family was lacking.…”
Section: Group Care May Cause Psychological Harm Even In Typically De...mentioning
confidence: 99%
“…Such linkages are predicted by cognitively-based theories of depression (Abramson et al, 1989;Beck, 1987;NolenHoeksema, 1990) and from earlier work indicating that mothers of infants with sleep problems worry more about their parenting competence, their ability to set limits at night, and about their infants' physical and emotional well-being (Morrell, 1999;Sadeh, Flint-Ofir, Tirosh, & Tikotsky, 2007). These cognitions in turn are associated with mothers' attempts to soothe infants to sleep and to co-sleep with them (Morrell & Steele, 2003;Tikotsky & Sadeh, 2009;Tikotzky, Sharabany, Hirsch, & Sadeh, 2010).…”
Section: Maternal Depression and Infant Night Wakingmentioning
confidence: 99%
“…49–51 There are few studies examining sleep-related cognition of both parents. 46 , 52 The only study analyzing data with respect to parental gender differences was conducted in Israel and found significant differences between mothers and fathers on the cognition scales, indicating that parents could hold different cognitions regarding their children’s demands during the night. 53 One main result of the study related to parental cognitions about potential difficulties in limit-setting parenting behavior - eg, resisting the child’s demands when it wakes up at night to help the child learn to fall asleep on its own - were found to be associated with poorer child sleep quality.…”
Section: Introductionmentioning
confidence: 99%